Further Dates of Heavy Metal Content on the Soil and Vegetation of Aggtelek Karst (Hungary) - Kaszala, Rita; Bárány-Kevei, Ilona; Polyák, Klára (Acta Carsologica, 2016)
O fizikalnih in kemičnih lastnostih prsti ter vsebnosti mikroelementov v rastlinju na območju Agteleškega krasa smo že poročali. V članku predstavimo nove meritve vsebnosti - v EDTA topnih - težkih kovin v prsti in meritve dodatnih elementov v različnih rastlinskih vrstah. Prikažemo tudi odnos med vsebnostjo težkih kovin v kraški prsti ter rastlinah in njihovimi poganjki. During the previous investigation of the Aggtelek Karst we published physical and chemical parameters of the soils and the microelement content of the greenery. The presentation now gives further information about the soil (e.g. EDTA soluble heavy metal content), and the greenery (more species, more elements). The presentation shows the relationship between the heavy metal content of the karstic soil, and the sprout of plants.